Evaluating spatially explicit sharing‐sparing scenarios for multiple environmental outcomes. Issue 3 (15th November 2020) - Finch, Tom; Day, Brett H.; Massimino, Dario; Redhead, John W.; Field, Rob H.; Balmford, Andrew; Green, Rhys E.; Peach, Will J.
Abstract: Understanding how to allocate land for the sustainable delivery of multiple, competing objectives is a major societal challenge. The land sharing‐sparing framework presents a heuristic for understanding the trade‐off between food production and biodiversity conservation by comparing region‐wide land‐use scenarios which are equivalent in terms of overall food production. Here, for two contrasting regions of lowland England (The Fens and Salisbury Plain), we use empirical data and predictive models to compare a suite of spatially explicit scenarios reflecting the full range of the sharing‐sparing continuum, including mixed scenarios which combine elements of both sharing and sparing. We evaluate a range of outcomes (bird populations, global warming potential (GWP), nitrogen and phosphorus pollution and outdoor recreation), to identify approaches to regional land‐use planning with the potential to deliver multiple societal benefits. Land‐sharing scenarios (which reduce the dominance of productive agricultural land in farmed areas and the area of larger unfarmed areas) result in negative outcomes, particularly for birds and GWP. In contrast, many land‐sparing scenarios (including mixed scenarios which increase the area of lower‐yield farmland alongside larger unfarmed areas) resulted in improvements in all or most outcomes, although for recreation and nutrient export differences between scenarios were modest. Importantly, environmental outcomes also depended on the spatial arrangement of spared land, the types of natural or semi‐natural habitat promoted on spared land, whether some lower‐yield farmland is delivered alongside larger unfarmed areas, and the overall region‐wide food production target. Policy implications . Our study suggests that land‐sparing strategies which increase the area of natural and semi‐natural areas can improve environmental outcomes, despite the costs associated with high‐yield agriculture. However, high‐yield agriculture should not compromise future production or the conservation value of spared land, and explicit policies such as certification or payments for ecosystem services are required to link sustainable high‐yield production to habitat conservation. Our study also highlights the importance of mitigating projected increases in food demand. Abstract : Our study suggests that land‐sparing strategies which increase the area of natural and semi‐natural areas can improve environmental outcomes, despite the costs associated with high‐yield agriculture. However, high‐yield agriculture should not compromise future production or ecosystem services on spared land, and explicit policies such as certification or payments for ecosystem services are required to link sustainable high‐yield production to habitat conservation. Our study also highlights the importance of mitigating projected increases in food demand.